The Arabs and Africa: By Khair El-Din Haseeb (EX) London: Croom Helm and Centre for Arab Unity Studies, 1985. 717 p. (American Journal of Islam and Society, 1987)
Since the beginning of decolonization in Africa in the late 1950’s Arabcountries have found it necessary to re-establish links with Africa south ofthe Sahara. An Arab leader like Gamal Abdel Nasser argued in his Philosophyof the Revolution (1954) that Africa constitutes the second circle in Egypt’sthree concentric circles of identity. The other two were the Arab and theIslamic. Nasser’s preoccupation with what he and his fellow Arab nationalistscalled the “Israeli menace”, was another factor which drove him to seek alliesand friends in Africa. But Nasser was not the first Arab leader to establishclose relations with the Africans. The Magrebians and the Arabians to theeast also forged links with Africa in the years before the primacy of Europein African political life.The book under review is one of a series of studies that have come outin the last decade. What distinguishes this work from those before it is itsfocus and its authors. In the early 1970’s when the Afro-Arab caravan beganto move rapidly along the pathways of international politics, many Westernand Third World intellectuals and scholars began to examine the nature ofwhat was then believed by many as a new phenomenon in international politics.Africa and the Middle Eastern states coexisted in the Bandung Movement;they journeyed together to the United Nations General Assembly, but up untilthe mid-1970’s closer bonds, which resulted in the greater coordination ofpolicies on major international issues, did not develop. In fact prior to the1973 massive defection of African states from the Israeli camp, most of theindependent African states were locked in diplomatic and political embracewith the Jewish state. Indeed, Africa was unique in the sense that it was theonly part of the Afro-Asian world where the Israelis received warm welcome.Israeli leaders tried hard to win friends and influence people in Asia but withoutsuccess. It is indeed against this background that the present book can beadequately reviewed.The work consists of the proceedings of a major conference held in Amman,Jordan on 24-29 April, 1983. Organized by the Centre for Arab UnityStudies, it brought together some sixty participants. Though the conferenceitself was conducted in Arabic, many of the participants suggested that theproceedings be published in English and French. This book is the English ...